Obshchestvennoe mnenie . Obshchestvennoe mnenie . Public Opinion . Общественное мнение - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Representatives of political parties and blocs of Russia explain, how they are going to solve socio-economic programs. Featured in the program: Chubais, Anatolii Borisovich (Politician); Shakhrai, Sergei Mikhailovich (Deputy Chairman of the Government of the Russian Federation); Zhirinovskii, Vladimir Vol'fovich (Politician); Ziuganov, Gennadii Andreevich (Politician); Fedulova, Alevtina Vasil'evna (Politician) Contributors: Proshutinskaia, Kira Aleksandrovna (Anchor) Представители политических партий и блоков России рассказывают, как они собираются решать социально-экономические проблемы. В программе участвуют: Чубайс, Анатолий Борисович (Политик); Шахрай, Сергей Михайлович (Заместитель Председателя Правительства Российской Федерации); Жириновский, Владимир Вольфович (Политик); Зюганов, Геннадий Андреевич (Политик); Федулова, Алевтина Васильевна (Политик) Создатели: Прошутинская, Кира Александровна (Ведущий/Ведущая)